Trade Openness And Service Sector For Income Tax Revenue: Exploring Government Expenditure’s Role Within - Wulandari, Destiny; Wijaya, Suparna (WIM Solusi Prima, 2024)
This study aims to examine the effect of trade openness and service sector on income tax revenue in East Asia and Pacific countries from 2008 to 2019. It was examined by setting government’s expenditure as a moderating variable and manufacturing sector and regulatory quality as control variables. It was performed by using a panel-corrected standard error (PCSE) model. The results of the study show that prior to moderation, trade openness has no significant effect, while the service sector has a significant negative effect on income tax revenue. After being moderated by government’s expenditure which has a significant positive effect on income tax revenue, the government’s expenditure moderates the effect of trade openness and the service sector on income tax revenue. However, the moderation only increases the trade openness’ effect on income tax revenue. The service sector’s effect on income tax revenue is reduced by the moderation. It implies that the optimization of income tax revenue can be carried out through government’s expenditure so that the trade openness and the service sector can be boosted. However, to prevent the negative effect of the service sector on income tax revenue, additional efforts are needed to make the informal sector from the service sector as the source of negative effect become the formal sector.